PREVENTIVE DETENTION IN INDIA: HISTORICAL BACKGROUND AND CONTEMPORARY ISSUES - Prakash, Tangirala Jaya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Aspects of law and Constitution which are contentious in India is preventive detention. From its colonial roots, its evolution apart from independence has mirrored that delicate tension between the liberty of the individual and the security requirement of the state. Highlights The historical origin of preventive detention from British colonial laws like the Defence of India Act, 1915 and the Government of India Act, 1935 to its constitutional adoption under Article 22. I understand that it was rolled out as urgent measure to ensure public order and national security however, the ongoing use of it even in peacetime poses big questions about the possibility of civil liberties and democratic accountability. Today, preventive detention laws like the National Security Act, 1980 and several state-specific ones are misused to house individuals without any charge or trial, often targeting the weaker sections of the society. The judiciary here is a mixed bag sometimes limiting executive excess but too often ruling detention is legal on technical grounds. This tension between national security and fundamental rights has become even more acute in the recent years with widespread concerns about arbitrary detention, abuse of power, and ineffective remedying mechanisms. Through a legal and political analysis, this article provides an overview of the human rights implications of the use of preventive detention in India. This demands a re-evaluation of the practice itself to bring it in line with both constitutional values and international human rights standards, and call for more transparency, judicial checks and balances and legislative reform as the case may be.